Association of BMI with adherence and outcome in heart failure patients treated with wearable cardioverter defibrillator - Mohammad Abumayyaleh; Katharina Koepsel; Julia W. Erath; Thomas Kuntz; Norbert Klein; Boldizsar Kovacs; Firat Duru; Ardan M. Saguner; Christian Blockhaus; Dong‐In Shin; Fabienne Kreimer; Michael Gotzmann; et al. (ESC Heart Failure)
Abstract Background Obesity is a known risk factor for cardiovascular disease (CVD), yet an ‘obesity paradox’ has been observed in various CVD contexts. The impact of obesity on heart failure (HF) patients treated with a wearable cardioverter‐defibrillator (WCD) remains underexplored. Methods In a multicentre international registry, we retrospectively collected data from a consecutive series of 1003 patients. These patients were divided into three body mass index (BMI) groups: <25 kg/m2 (n = 348), 25–30 kg/m2 (n = 383), and >30 kg/m2 (n = 272), with BMI > 30 kg/m2 defined as the reference category. Demographics, indications, adherence, WCD shocks, arrhythmic events, rehospitalization due to cardiovascular causes, and mortality were analysed. Results At 3 month follow‐up, patients with a BMI > 30 showed the greatest improvement in left ventricular ejection fraction (LVEF) at 51.4%, significantly higher than the 41.4% in those with a BMI < 25 (P = 0.017) and comparable with the 49.4% in the BMI 25–30 group (P = 0.635). WCD wearing time and adherence were similar across all BMI groups. The incidence of WCD shock was similar across BMI groups. Rates of ventricular tachycardia (VT), ventricular fibrillation and non‐sustained VT (ns‐VT) were comparable across BMI groups. The rate of implantable cardioverter‐defibrillator (ICD) implantation was 40.3% across all patients, with a slightly lower rate in the BMI > 30 group (36.8%) compared with others, although not significantly. Rehospitalization due to cardiovascular causes was significantly lower in the BMI > 30 group (55.4%) compared with the BMI 25–30 group (70.9%; P = 0.048), but similar to the BMI < 25 group (54.9%; P = 0.957). At 2 year follow‐up, mortality was lower in the BMI > 30 group (5.9%) compared with the BMI < 25 (7.5%; P = 0.029) and BMI 25–30 groups (7%; P = 0.681). In multivariable analysis, LVEF at long term was significantly associated with a reduction in mortality. Conclusions Obese patients exhibited significantly greater improvement in LVEF, which was associated with reduced mortality. Adherence to WCD therapy was excellent across all BMI groups. ICD implantation occurred in 40.3% of patients, with similar WCD shock rates and arrhythmic events across BMI groups. An obesity paradox was observed, with obese patients demonstrating significantly lower rehospitalization rates due to cardiovascular causes and reduced mortality at follow‐up.